Transcriptomic analysis of genes related to alkaloid biosynthesis and the regulation mechanism under precursor and methyl jasmonate treatment in Dendrobium officinale - Jiao, Chunyan; Wei, Mengke; Fan, Honghong; Song, Cheng; Wang, Zhanjun; Cai, Yongping; Jin, Qing (Frontiers in Plant Science, 2022)
Dendrobium officinale is both a traditional herbal medicine and a plant of high ornamental and medicinal value. Alkaloids, especially terpenoid indole alkaloids (TIAs), with pharmacological activities are present in the tissues of D. officinale. A number of genes involved in alkaloid biosynthetic pathways have been identified. However, the regulatory mechanisms underlying the precursor and methyl jasmonate (MeJA)-induced accumulation of alkaloids in D. officinale are poorly understood. In this study, we collected D. officinale protocorm-like bodies (PLBs) and treated them with TIA precursors (tryptophan and secologanin) and MeJA for 0 (T0), 4 (T4) and 24 h (T24); we also established control samples (C4 and C24). Then, we measured the total alkaloid content of the PLBs and performed transcriptome sequencing using the Illumina HiSeq 2500 system. The total alkaloid content increased significantly after 4 h of treatment. Go and KEGG analysis suggested that genes from the TIA, isoquinoline alkaloid, tropane alkaloid and jasmonate (JA) biosynthetic pathways were significantly enriched. Weighted gene coexpression network analysis (WGCNA) uncovered brown module related to alkaloid content. Six and seven genes related to alkaloid and JA bisosynthetic pathways, respectively, might encode the key enzymes involved in alkaloid biosynthesis of D. officinale. Moreover, 13 transcription factors (TFs), which mostly belong to AP2/ERF, WRKY, and MYB gene families, were predicted to regulate alkaloid biosynthesis. Our data provide insight for studying the regulatory mechanism underlying TIA precursor and MeJA-induced accumulation of three types of alkaloids in D. officinale.